2011
DOI: 10.1002/ange.201101227
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Directs Multiple Radical Additions to the 9,9′‐Bi‐1‐aza(C60Ih)[5,6]fullerene: X‐ray Structure of 6,9,12,15,18‐C59N(CF3)5

Abstract: Gestapelt wie Pappbecher: Moleküle des ersten strukturell aufgeklärten (C59N)2‐Derivats, das Trifluormethyl‐Gruppen trägt, stapeln mit einem Abstand von 10.179 Å senkrecht aufeinander und bilden so eine seltene, nicht dicht gepackte Anordnung (AAA…︁; siehe Bild). Die Gegenwart von Stickstoff im Fulleren‐Grundgerüst führt zu einzigartigen Additionsmustern in C59N(CF3)7/9/11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…The N atom is disordered over the five equivalent positions of the isolated pentagon owing to the overlap of five molecules rotated by 72° relative to each other. The same feature was observed in the single‐crystal structure of C 59 N(CF 3 ) 5 3d. The average bond lengths within the pyrrole ring, at 1.40 Å, are comparable to the average bond length of 1.38 Å in pyrrole 13.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…The N atom is disordered over the five equivalent positions of the isolated pentagon owing to the overlap of five molecules rotated by 72° relative to each other. The same feature was observed in the single‐crystal structure of C 59 N(CF 3 ) 5 3d. The average bond lengths within the pyrrole ring, at 1.40 Å, are comparable to the average bond length of 1.38 Å in pyrrole 13.…”
Section: Methodssupporting
confidence: 78%
“…through a complex sequence of reactions and rearrangements starting from a cage‐opened oxafulleroid prepared from C 60 3c. More recently, this pentaaddition pattern was obtained upon reaction of (C 59 N) 2 with trifluoromethyl iodide where C 59 N(CF 3 ) 5 was formed among other higher adducts and characterized by X‐ray single‐crystal analysis 3d…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the groups of Sokolov, as well as Matsuo and Nakamura, have reported the crystal structure of 6,9,12,15,18‐pentamethyl‐1‐hydro‐[60]fullerene ( 1 , R=CH 3 ) as an example of one of the smallest stacking fullerenes (Figure 1a) 19. Sokolov suggested that the formation of columnar stacks is general and independent of the nature of the addend 20. However, we have found that a number of pentaarylfullerenes form nonstacked motifs (Scheme , Table 2), which indicates that stacking is far from general in these compounds.…”
Section: Resultsmentioning
confidence: 76%
“…Accordingly, phenyl groups with relatively large and spheroidal substituents at the 4‐position are the best suited to promote stacking, as determined experimentally from their crystal structures (vide infra), whereas small addends (e.g., 1 , R=CH 3 or Ph, Figure 2a, b) give sockets with a cavity that can be too shallow for efficient stacking 19. 20…”
Section: Resultsmentioning
confidence: 99%
“…The resulting molecule, a heterofullerene, acquires electronic structure that is distinct from its all‐carbon precursor. Therefore, modification of electronic and optical properties by heteroatom doping is a promising route toward devising, for example, fullerene‐based molecular electronics, solar cells, and hydrogen‐storage technologies, as well as exploring new fullerene chemistry 714. Preferred elements for fullerene doping are trivalent heteroatoms that most closely resemble carbon in size and electronegativity, because such elements are most likely to exhibit covalent bonding in a fullerene.…”
Section: Ionization Energies (Ie) and Electron Affinities (Ea) Alongmentioning
confidence: 99%